Six decades of North American bird banding records reveal plasticity in migration phenology. Issue 3 (30th January 2023) - Horton, Kyle G.; Morris, Sara R.; Van Doren, Benjamin M.; Covino, Kristen M.
Abstract: The timing of avian migration has evolved to exploit critical seasonal resources, yet plasticity within phenological responses may allow adjustments to interannual resource phenology. The diversity of migratory species and changes in underlying resources in response to climate change make it challenging to generalize these relationships. We use bird banding records during spring and fall migration from across North America to examine macroscale phenological responses to interannual fluctuations in temperature and long‐term annual trends in phenology. In total, we examine 19 species of North American wood warblers (family Parulidae), summarizing migration timing from 2, 826, 588 banded birds from 1961 to 2018 across 46 sites during spring and 124 sites during fall. During spring, warmer spring temperatures at banding locations translated to earlier median passage dates for 16 of 19 species, with an average 0.65‐day advancement in median passage for every 1°C increase in temperature, ranging from 0.25 to 1.26 days °C −1 . During the fall, relationships were considerably weaker, with only 3 of 19 species showing a relationship with temperature. In those three cases, later departure dates were associated with warmer fall periods. Projecting these trends forward under climate scenarios of temperature change, we forecast continued spring advancements under shared socioeconomic pathways from 2041 to 2060 and 2081 to 2100 and more muted and variable shifts for fall. These results demonstrate the capacity of long‐distance migrants to respond to interannual fluctuations in temperatures, at least during the spring, and showcase the potential of North American bird banding data understanding phenological trends across a wide diversity of avian species. Abstract : The authors use a critically underutilized resource—bird banding data—to quantify and forecast changes in spring and fall migration across North America to ask the question of how migrants respond to macroscale phenological responses in interannual fluctuations in temperature.